2009
DOI: 10.1007/s11631-009-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic susceptibility of the Xifeng section and its paleoclimate significance

Abstract: Magnetic susceptibility (MS) is one of the most important indicators of the East-Asia summer monsoon. Presented in this study is a high resolution magnetic susceptibility record from the Xifeng section, which consists of Quaternary loess-paleosol sequence and Pliocene red clay. Variations in magnetic susceptibility are well correlated with the δ 18 O record in deep-sea sediments and the eolian flux of Greenland. The climatic evolution in the Xifeng section shows that since the Late Tertiary, the driving force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…If we accept that the MBB is between the two paleosols (U2-S7 and U2S8) then the displacement could indicate the socalled lock-in depth effect noted in other Chinese and Danubian loess profiles as well (Zhou and Shackleton, 1999;Markovi c et al, 2011Markovi c et al, , 2015Murray et al, 2014). A similar depth and position for the MBB was noted for the Xifeng loess section above loess unit 8 (L8) at a depth of 71 m. Later a higher position of MBB above the S8 pedocomplex and the bottom of S7 was proposed at a depth of 69 m for this profile (Liu et al, 1987(Liu et al, , 1988Guo et al, 2011Guo et al, , 2009ab;Sun et al, 2009;Wu and Wu, 2011). The displacement of the MBB from the top of L8 towards the bottom of S7 have been noted by Zhou and Shackleton (1999) blaming the so-called lock-in effect for the original position of the boundary.…”
Section: Magnetostratigraphysupporting
confidence: 66%
See 3 more Smart Citations
“…If we accept that the MBB is between the two paleosols (U2-S7 and U2S8) then the displacement could indicate the socalled lock-in depth effect noted in other Chinese and Danubian loess profiles as well (Zhou and Shackleton, 1999;Markovi c et al, 2011Markovi c et al, , 2015Murray et al, 2014). A similar depth and position for the MBB was noted for the Xifeng loess section above loess unit 8 (L8) at a depth of 71 m. Later a higher position of MBB above the S8 pedocomplex and the bottom of S7 was proposed at a depth of 69 m for this profile (Liu et al, 1987(Liu et al, , 1988Guo et al, 2011Guo et al, , 2009ab;Sun et al, 2009;Wu and Wu, 2011). The displacement of the MBB from the top of L8 towards the bottom of S7 have been noted by Zhou and Shackleton (1999) blaming the so-called lock-in effect for the original position of the boundary.…”
Section: Magnetostratigraphysupporting
confidence: 66%
“…So, using the characteristic MS pattern as a stratigraphic tool along with the newly established chronology, litho-and pedostratigraphy, our records were correlated with the regional records of similar age in Hungary (Paks) (P ecsi, 1995;Frechen et al, 1997;Sartori, 2000;Thiel et al, 2014;Újv ari et al, 2014a), Serbia (Stari Slankamen, Batajnica, Mo sorin, Ruma) (Markovi c et al, 2006(Markovi c et al, , 2009(Markovi c et al, , 2011(Markovi c et al, , 2015, Bulgaria (Koriten, Viatovo) (Jordanova and Petersen, 1999;Jordanova et al, 2007Jordanova et al, , 2008 Romania (Mostistea, Mircea Voda, Zimnicea) (Panaiotu et al, 2001;Buggle et al, 2009Buggle et al, , 2013R adan, 2012). In addition, cross-correlation was attempted with other long-known and studied Chinese LPS of Xifeng (Liu et al, 1987(Liu et al, , 1988Lu et al, 2004;Guo et al, 2009a;b;Sun et al, 2009;Wu and Wu, 2011;Zhang et al, 2015) using a synthesis stratigraphical column based on the U2-A borehole sequence.…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations
“…It is therefore possible to use magnetic susceptibility as a proxy for terrigenous sediment supply (De Menocal et al, 1991). It is widely used in a variety of marine and terrestrial settings as an indicator of changing environmental conditions and thus climate in the Asian monsoon region (e.g., De Menocal et al, 1991;Kumar et al, 2005;Thamban et al, 2005;Yancheva et al, 2007;Sun et al, 2009). It has been shown that increasing values of magnetic susceptibility correlate with periods of strengthening monsoon, as reconstructed from oxygen isotope records, revealing a link between Eolian transport and strong East Asian Winter Monsoon winds (An et al, 2001).…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%